Redistributivna pravičnost v slovenskem sistemu socialne varnosti - Kopač, Anja (Družboslovne razprave, 2010)
The changing socio-economic context, especially the labour market's structure, the process of globalisation, demographic shifts and changes in the informal sphere of life are straining the relationship between the labour market and social protection schemes and leading to a search for a new balance that would provide economic efficiency and social security. The paper's authors analyse changes in the Slovenian social protection scheme for unemployed people during the last two decades and their effects in practice. The analysis focuses on the redistributive principles implemented in the scheme. They determine the fundamental goals of the redistribution, its mechanisms and institutional variables and, as such, define the nature of social policy and its outcomes (e.g. poverty, social exclusion, social inequality).
Keywords: Social security; Socialna varnost; Unemployed; Brezposelni; Justice; Pravičnost; Slovenia; Slovenija; socialna politika